Impact of Quadriceps/Hamstrings Torque Ratio on Three-Dimensional Pelvic Posture and Clinical Pubic Symphysis Pain-Preliminary Results in Healthy Young Male Athletes - Oliver Ludwig; Jens Kelm; Sascha Hopp (Applied Sciences, 2020)
Pain in the pubic symphysis is of significance, especially in high-performance sports. Pelvic torsion, possibly caused by muscular imbalances, is discussed as a pathogenic mechanism. This study examined a possible interrelationship between the maximum torques of quadriceps femoris and hamstrings and the spatial positioning of the hemi-pelvises, as well as the tenderness to palpation of the pubic symphysis. The three-dimensional pelvic contour of 26 pain free adolescents (age 16.0 ± 0.8 years, weight 66.3 ± 9.9 kg, height 176.2 ± 6.0 cm) was registered by means of an 3D optical system and the torsion of both hemi-pelvises against each other was calculated based on a simplified geometrical model. Tenderness on palpation of the pubic symphysis was assessed by means of a visual analogue scale, and isometric torques of knee extensors and flexors were measured for both legs. The torque ratio between knee extensors and flexors was calculated for both sides, as was the crossed torque ratio between the two legs. On the basis of a MANOVA, possible significant differences in torques and torque ratios between subgroups with lower and higher pelvic torsion were analyzed. The crossed torque ratio (F = 19.55, p < 0.001, partial η2 = 0.453) and the tenderness to palpation of the pubic symphysis (F = 10.72, p = 0.003, partial η2 = 0.309) were significantly higher in the subgroup with higher pelvic torsion. The results indicate the crossed torque ratio of knee flexors and extensors as a potential biomechanical-pathogenic mechanism to be considered in the primary prevention and diagnosis of symphyseal pain.